Modification of Sulfadiazine Antibacterial to Promising Anticancer Schiff Base Derivatives: Synthesis and in Vitro Studies - Tasnim Tariq Mohammed; Aula Hassoon Obaid; Ghasaq Farouq Hammeed; Abbas K. Abbas (The International Science of Health Journal, 2024)
The study displays a novel approach for synthesizing imine-sulfadiazine compounds (A and B) by reacting Sulfadiazine with various aldehydes, including 2-chlorobenzaldehyde and 4-pentoxybenzaldehyde. The derivatives (A and B) were characterized using spectroscopic techniques, specifically FT?IR spectroscopy. The synthesized compounds were assessed in vitro against various bacteria, including Streptococcus pneumoniae and E. coli, using the zone inhibition method. The results indicated that specific derivatives possess enhanced antibacterial characteristics compared to the effectiveness of the regular medications. The derivative A was assessed for its anticancer activity against breast cancer MCF-7 cells using the MTT assay, which yielded a favorable outcome within 24 hours.